Companion Animals in the Everyday Life of Residents of Modern Cities - Lubiarz, Magdalena (Roczniki Kulturoznawcze, 2024)
People’s attitudes towards animals depend on cultural and social factors and conditions. Relationships between humans and animals have evolved over the centuries and continue to change. Undoubtedly, the relationship between humans and companion animals has many benefits, from improved physical and mental health, to positive effects on learning skills, as well as the development of social skills and interpersonal relationships. In this perspective, the presence of pets, especially dogs, is becoming more and more visible in urban areas. The needs of dog owners and their pets influence the design of urban spaces, while animals and their impact on people and the environment are even seen as nature-based solutions.